Pelaksanaan Pelayanan Kesehatan Puskesmas Oleh Dinas Kesehatan Kota Batam - Ulima Harma Ulima Harma; Azhar Abbas; Aprillia Aprillia (Dialektika Publik, 2019)
The health center is the first level implementing unit from the Health Office which is responsible for the implementation of health development in a work area. The purpose of this research is to knowing the implementation of health services for health center by the Health Service in Batam city. This research is a descriptive with qualitative approach. The results show there are 20 Number of health center in Batam City based on data obtained from the Batam City Health Service. As a whole, there were 20 health workers who still lacked 20 health workers, 3 health analysts, 3 health workers and 3 health workers and 1 health worker. Furthermore, Health Workers who exceed the needs of the health center, namely the Pharmacists as many as 2 Health Workers and as many as 19 Pharmaceutical Technical Workers (TTK). And the inhibiting factor for the implementation of Batam City health services lies in the lack of medical personnel in the health center so that the health center is only able to provide Health Services to the community in accordance with the availability of existing medical personnel and this affects the low quality of services.